Cardiovascular pre-participation screening in the young athlete: addressing concerns - Raukar, N.; Arciero, E.; Noyes, A.; Drezner, J.; Weiss, J. (The Physician and Sportsmedicine, 2017)
The incidence of sudden cardiac death (SCD) in young athletes has been estimated as low as 1:917,000 in high school athletes in the USA [1]. However, the rate of SCD is significantly higher in certain young athlete populations, such as male college basketball players, where the rate has been reported as high as 1:5,200 athlete years [2]. The wide range of SCD incidence is related to differences in study methodology and the accuracy of case capture and population estimates. In general, an accepted overall rate of SCD in young athletes in the USA is approximately 1:50,000-80,000 per year [3]. To identify those at risk for catastrophic injury and death, young athletes in the USA undergo a pre-participation screening exam consisting of a history questionnaire and a physical exam [4].